The impact of the worldwide Millennium Development Goals campaign on maternal and under-five child mortality reduction: 'Where did the worldwide campaign work most effectively?' - Seungman Cha (Taylor & Francis Group, 2017)
Background: As the Millennium Development Goals campaign (MDGs) came to a close, clear evidence was needed on the contribution of the worldwide MDG campaign. Objective: We seek to determine the degree of difference in the reduction rate between the pre-MDG and MDG campaign periods and its statistical significance by region. Design: Unlike the prevailing studies that measured progress in 1990-2010, this study explores by percentage how much MDG progress has been achieved during the MDG campaign period and quantifies the impact of the MDG campaign on the maternal and under-five child mortality reduction during the MDG era by comparing observed values with counterfactual values estimated on the basis of the historical trend. Results: The low accomplishment of sub-Saharan Africa toward the MDG target mainly resulted from the debilitated progress of mortality reduction during 1990-2000, which was not related to the worldwide MDG campaign. In contrast, the other regions had already achieved substantial progress before the Millennium Declaration was proclaimed. Sub-Saharan African countries have seen the most remarkable impact of the worldwide MDG campaign on maternal and child mortality reduction across all different measurements. In sub-Saharan Africa, the MDG campaign has advanced the progress of the declining maternal mortality ratio and under-five mortality rate, respectively, by 4.29 and 4.37 years. Conclusions: Sub-Saharan African countries were frequently labeled as 'off-track', 'insufficient progress', or 'no progress' even though the greatest progress was achieved here during the worldwide MDG campaign period and the impact of the worldwide MDG campaign was most pronounced in this region in all respects. It is time to learn from the success stories of the sub-Saharan African countries. Erroneous and biased measurement should be avoided for the sustainable development goals to progress.